Pengaruh Manajemen Laba Akrual, Ukuran Perusahaan, Kualitas Audit, dan Profitabilitas terhadap Kualitas Laba pada Perusahaan Manufaktur - Muliani, Upekha Tri; Mahroji, Mahroji (Jurnal EMT KITA, 2026)
In an increasingly complex business environment, earnings quality is influenced not only by operational performance but also by various internal and external factors of a company. This study aims to analyze the effect of accrual earnings management, firm size, and audit quality on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2021 to 2023. Earnings quality is an important indicator in evaluating a company's financial performance and serves as a basis for investors' decision-making. This research employs a quantitative approach using multiple linear regression analysis. The sample was selected using purposive sampling, with secondary data derived from companies’ annual financial reports. Based on agency theory, there is a conflict of interest between managers and owners, which encourages managers to maximize earnings quality by utilizing various internal and external factors. Accrual earnings management, audit quality, profitability and firm size serve as external monitoring mechanisms to mitigate conflicts between managers and owners. The results indicate that accrual earnings management has a positive and significant effect on earnings quality. However, firm size and audit quality do not have a significant effect on earnings quality. Nevertheless, simultaneously, all three independent variables are proven to have a significant effect on earnings quality. These findings suggest that accrual management practices play a crucial role in enhancing the quality of earnings information, while firm size and audit quality have not yet made a meaningful contribution in this context. This study has implications for companies to adopt greater transparency in financial reporting practices, and for investors to consider internal factors affecting earnings quality. The results are also expected to serve as an academic reference for future research in the field of financial accounting.